Assessing the influence of social media platforms on the brand awareness of PLM Business School Students - Amican, Joyce Ann P. Dionisio, Alliah Mae A. Estopace, Abegail E. Figuiroa, Angelika S. Mendoza, Mykah N. 4 0 16; 5 (2023)
ABSTRACT Fast fashion's dominance has impacted Filipino consumer behavior, influencing how they buy clothes. Understanding these preferences is crucial for businesses to choose the best sales stores. This study explores the shopping preferences of 3rd-year marketing students in Pamantasan ng Lungsod ng Maynila towards traditional and online fast-fashion stores. The research used a survey to compare student experiences with online and traditional stores in five areas: shopping experience, brand perception and loyalty, return & exchange policies, security & trust, and social media influence. The goal was to see if students had a stronger preference for one type of store. By employing a comparative research design with a survey approach, this study aims to gain a deeper understanding of the factors that differentiate student preferences between traditional and online fast-fashion stores. The researchers utilized the non-parametric test Mann-Whitney U in comparing the respondents' experiences with online and traditional shopping and to determine if there is a significant difference. The results identified significant differences only in return & exchange policies and security & trust, favoring traditional stores. Interestingly, no significant differences emerged in shopping experience, brand perception and loyalty, or social media influence. This suggests that students might prioritize convenience and trust more than other factors when choosing a fast-fashion store. The study highlights the importance of consumer trust, satisfaction, and security for businesses to thrive in the fast-fashion industry. Additionally, it emphasizes the need for social media platforms to provide secure environments for both consumers and businesses. Since our study looked at both traditional and online stores, it can contribute to adapting the TPB framework for different shopping situations. The importance of attitudes, subjective norms, and perceived behavioral control might differ depending on whether students considering about online stores or traditional stores. By understanding the preferences of marketing students for traditional and online fast-fashion stores, businesses can develop targeted marketing strategies. This can involve optimizing online presence, enhancing the in-store experience, or creating campaigns that resonate with young consumers. Keywords: Traditional stores, Online Stores, Fast-fashion.
Business Research: (BSBA major in Marketing Management) - Pamantasan ng Lungsod ng Maynila, 2024.
Keywords: 2 -- 0; 6; 20; 20; 2